High-dose postpartum thromboprophylaxis in women at high risk of pregnancy-related venous thromboembolism: a single-center prospective cohort study - Sean C.S. Rivrud; Èmese R.H. Heijkoop; Marloes A.G. Holswilder–Olde Scholtenhuis; Karina Meijer (Research and Practice in Thrombosis and Haemostasis)
Background: Pregnancy-related venous thromboembolism (VTE) is a major cause of maternal mortality and morbidity. While thromboprophylaxis can reduce the incidence of VTE, it may increase the risk of bleeding. Current guidelines recommend assessing VTE risk in pregnant women and administering low-molecular-weight heparin (LMWH) thromboprophylaxis to those at high risk. However, there is a paucity of evidence regarding the optimal dosing of postpartum LMWH thromboprophylaxis. Objectives: To evaluate the safety and efficacy of fixed low-dose LMWH antepartum and weight-based high-dose LMWH (equivalent to weight-based therapeutic-dose LMWH) until 6 weeks postpartum in a prospective cohort of women at high risk for pregnancy-related VTE. Methods: From December 8, 2014, to November 9, 2023, we included patients at high risk for pregnancy-related VTE who required thromboprophylaxis during pregnancy and the puerperium. The primary safety outcome was the incidence of primary and secondary major postpartum hemorrhage. The secondary safety outcome was the incidence of primary and secondary postpartum clinically relevant nonmajor bleeding (CRNMB). The efficacy outcome was the incidence of VTE. Additional outcomes included treatment discontinuation and treatment modification. Results: We found a 6.56% incidence of primary major postpartum hemorrhage, a 9.84% incidence of primary postpartum CRNMB, a 5.00% incidence of secondary postpartum CRNMB, a 3.33% incidence of VTE, a 16.1% incidence of treatment discontinuation, and a 30.6% incidence of treatment modification. Conclusion: When evaluating the optimal dose of thromboprophylaxis, the acceptable residual risk of VTE is debatable but should be considered in conjunction with the risks of adverse events, particularly bleeding and drug reactions, such as hypersensitivity skin reactions.